Environmental impact analysis : process and methods - Maughan, James T., 1949- (Boca Raton, FL : CRC Press, 2013)
'This book provides a comprehensive description of the environmental analysis and approval process. It describes the methods and tools available to successfully accomplish the analysis and includes a step-by-step description of how to prepare an environmental analysis document that meets technical, regulatory, and stakeholder expectations and requirements. Case studies drawn from author's long experience with preparation and review of environmental analyses illustrate each step. The text details the regulatory mandates and identifies approaches for prediction of impacts, interaction with stakeholders, comparison of alternatives, and obtaining regulatory approval and public acceptance.'--
Includes bibliographical references and index.
Keywords: Environmental impact analysis -- United States -- Handbooks, manuals, etc